2019
DOI: 10.1093/mnras/stz3012
|View full text |Cite
|
Sign up to set email alerts
|

Carina’s pillars of destruction: the view from ALMA

Abstract: Forming high-mass stars have a significant effect on their natal environment. Their feedback pathways, including winds, outflows, and ionising radiation, shape the evolution of their surroundings which impacts the formation of the next generation of stars. They create or reveal dense pillars of gas and dust towards the edges of the cavities they clear. They are modelled in feedback simulations, and the sizes and shapes of the pillars produced are consistent with those observed. However, these models predict me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…The pillar regions are considerably smaller (∼ 0.4 pc) and thus have only mildly supersonic velocity dispersions (M ∼ 2-4). The obtained velocity dispersions (M × c s ) are in the range 0.4-1 km s −1 , in agreement with observations of pillars on these scales (Klaassen et al 2019).…”
Section: Pillar Regionssupporting
confidence: 90%
See 2 more Smart Citations
“…The pillar regions are considerably smaller (∼ 0.4 pc) and thus have only mildly supersonic velocity dispersions (M ∼ 2-4). The obtained velocity dispersions (M × c s ) are in the range 0.4-1 km s −1 , in agreement with observations of pillars on these scales (Klaassen et al 2019).…”
Section: Pillar Regionssupporting
confidence: 90%
“…Figure 1 shows that the tips of the pillars have the highest density enhancements. It is at these pillar tips that star formation is observed to occur (e.g., Smith et al 2010;Reiter & Smith 2013;Klaassen et al 2014Klaassen et al , 2019. Thus, we define three different pillar regions for more detailed analysis below: Pillar A, B and C of sizes 0.4 pc in each direction.…”
Section: Gas Structure and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared to submillimeter images (see Smith et al 2010;Preibisch et al 2012Preibisch et al , 2011c revealed numerous pillar-like cloud structures in the southern parts of the Carina Nebula. Such pillars are thought to be a natural outcome of the feedback from strong ionizing radiation fields on clouds (see, e.g., Gritschneder et al 2010;Dale et al 2013;McLeod et al 2016;Klaassen et al 2020). While almost all pillars in the Carina Nebula point toward the massive stars around η Car in Tr 16, the Spitzer image (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Expanding H regions are known to sculpt the surrounding neutral gas in the ISM into structures reminiscent of the iconic 'Pillars of Creation' imaged by the Hubble Space Telescope (Hester et al 1996). There have been a wealth of observations that image these pillars and related structures such as globules, energetic evaporating globules (EEG's) and proplyds, to deduce dynamical quantities in and around them (Preibisch et al 2012;Mann et al 2014;Grenman & Gahm 2014;Klaassen et al 2014;Hartigan et al 2015;Schneider et al 2016b;Djupvik et al 2017;Klaassen et al 2018;Reiter et al 2019;Klaassen et al 2019). Models proposed to explain their formation fall broadly into two categories: the classic collect-and-collapse model by Elmegreen & Lada (1977), where the H region sweeps up and accumulates cold gas, creating density enhancements and eventually pillars in their shadows; or the more recent radiation-driven implosion (RDI) model, where clouds with pre-existing density enhancements are sculpted to form pillars by impinging ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%